miRNA Expression Profiling Uncovers a Role of miR-139-5p in Regulating the Calcification of Human Aortic Valve Interstitial Cells - Zhang, Fan; Cheng, Naixuan; Han, Yingchun; Zhang, Congcong; Zhang, Haibo (Frontiers in Genetics, 2021)
Calcific aortic valve disease (CAVD) is the most common structural heart disease, and the morbidity is increased with elderly population. Several microRNAs (miRNAs) have been identified to play crucial roles in CAVD, numerous miRNAs are still waiting to be explored. In this study, the miRNA expression signature in CAVD was analyzed unbiasedly by miRNA-sequencing, and we found that, compared with the normal control valves, 152 miRNAs were up-regulated and 186 miRNAs were down-regulated in calcified aortic valves. The functions of these differentially expressed miRNAs were associated with cell differentiation, apoptosis, adhesion and immune response processes. Among down-regulated miRNAs, the expression level of miR-139-5p was negatively correlated with the osteogenic gene RUNX2, and miR-139-5p were also down-regulated during the osteogenic differentiation of primary human aortic valve interstitial cells (VICs). Subsequent functional studies revealed that miR-139-5p overexpression inhibited the osteogenic differentiation of VICs by negatively modulating the expression of pro-osteogenic gene FZD4 and CTNNB1. In conclusion, these results suggest that miR-139-5p plays an important role in osteogenic differentiation of VICs via Wnt/b-Catenin pathway, which may further provide a new therapeutic target for CAVD.